ALANG “LUMBUNG PADI” DAN STATUS SOSIAL PADA MASYARAKAT TORAJA DI LEMBANG BENTENG KA’DO - Merianti Tampang; Veronika E.T Salem; Hamdi Gugule (Labor Program Studi Pendidikan Sosiologi, 2020)
The purpose of this study was to determine the public perception of the social status of Alang owners in Toraja society and to determine the function of Alang in Toraja society. The problem in this research is the public perception of the social status of the owner of the Lumbung Padi Alang in the Toraja community. The research method used is qualitative research. The research method that aims to provide a systematic, factual and accurate description. By using library research data collection techniques, field research and documentation. The results in the field show that the Alang Culture and Social Status in the Toraja people are still maintained. One of them is Alang